1972
DOI: 10.1126/science.175.4022.656
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Renin-Angiotensinogen Reaction by Pepstatin

Abstract: Pepstatin, an N-acylated pentapeptide obtained from culture filtrates of actinomycetes and first characterized as an inhibitor of pepsin, produces inhibition of the renin-substrate reaction both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

1974
1974
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(30 citation statements)
references
References 5 publications
1
28
0
1
Order By: Relevance
“…2). The value of K i was more than 60 times higher than that of K m and was much higher than that of other potent renin inhibitors (32,33). The K m was in the similar range as reported previously (24).…”
Section: Discussionsupporting
confidence: 68%
“…2). The value of K i was more than 60 times higher than that of K m and was much higher than that of other potent renin inhibitors (32,33). The K m was in the similar range as reported previously (24).…”
Section: Discussionsupporting
confidence: 68%
“…To determine whether cellular Al generation was dependent on the activity of intracellular aspartyl proteases, we evaluated the effect of pepstatin, the specific inhibitor for these enzymes (Gross et al, 1972). Cellular sonicates were incubated at 37°C with 0.1-1 DIM pepstatin at pH 5.5 for 1 hour.…”
Section: Characterization and Identification Of Cellular Renin-like Amentioning
confidence: 99%
“…Proof of principle was established first by use of immunization against renin, 14 followed by studies with a nonspecific inhibitor, pepstatin, and finally with peptide mimics of either prorenin or of the renin substrate angiotensinogen. 15,16 Several of the peptide mimics were developed as possible drugs, and the invaluable knowledge gained has already been well described in the review of renin inhibitors by Staessen et al 17 Parenteral administration of peptide inhibitors to salt-depleted subjects confirmed proof of principle as an effective mechanism of blood pressure reduction, 18 and the development of tetrapeptides led to clinical investigation of orally administered compounds (enalkiren, remikiren, zankiren). 19 However, these compounds had predictably low bioavailability of Ͻ2% and short half-lives.…”
Section: The Target For Direct Renin Inhibitionmentioning
confidence: 99%